Groundwater Market in West Bengal, India: Does it Display Monopoly Power?. (June 2018) - Acharyya, Achiransu; Ghosh, Madhusudan; Bhattacharya, Rabindra N.
Abstract: Based on village-level primary household survey in three districts of West Bengal, the present study tries to understand the groundwater market structure using the standard market theory. Comparing the internal rate of return of private investors on groundwater irrigation with past studies, it is found that although the degree of monopoly has gone down in the state over time, a certain element of monopoly still exists in the groundwater market. The estimates of price-to-marginal cost ratios and the Lerner index amply demonstrate the existence of high degree of monopoly in groundwater market. The study also shows that since banks give loans based on collateral, it is the large farmland owners who benefit from these bank loans for installation of electric submersibles for groundwater irrigation. Factors such as availability of rain and canal water, advance payment for water, distance of the land from the irrigation source, and maintenance and labour cost of water extraction mechanism also affect the price of water. As the groundwater extraction increases, it leads to lowering of the groundwater table leading to increasing cost for the water seller who in effect transfers the increasing cost to price leading to a rise in groundwater prices. This is a cause of concern not only for the small and marginal farmers but also for the sustainability of groundwater. JEL Classifications: Q15, D42, Q21